Highly‐Dispersed Ni‐QDs/Mesoporous Carbon Nanoplates: A Universal and Commercially Applicable Approach Based on Corn Straw Piths and High Capacitive Performances. Issue 12 (2nd September 2015) - Su, Liwei; Hei, Jinpei; Wu, Xianbin; Wang, Lianbang; Wang, Yuanhao
Abstract: Metal and metal oxides are extremely competitive in various applications such as catalysis and energy storage, while the intrinsically unsatisfactory ion/electron conductivity and/or large volume swing severely inhibit their inherent potentials. Quantum dots (QDs) can significantly promote the conductivity, buffer volume variation, and introduce novel physical/chemical properties, especially in cooperation with mesoporous carbon (MC), and hence are attracting ever‐increasing attention. However, it is still a worldwide challenge to exploit a facile, efficient, environmentally benign, commercially applicable, and, in particular, universal method for varied QDs/MC hybrids. In this work, a powerful approach is proposed on basis of corn straw piths, and a synthetic mechanism is proposed and investigated systematically. According to this route, Ni, Co, Cu, and MnO QDs/MC nanoplates are successfully fabricated. As a typical example, ultrasmall Ni QDs (5–7 nm) are homogeneously distributed on the large surface of MC nanoplates and exhibit a reversible capacitance of 2420 F g −1 at 500 mA g −1 and rate performance. This work discloses a new and paramount path to exploit versatile QDs/MC hybrids for promising applications such as lithium ion batteries, solar cells, Li–air batteries, and other promising fields with electrochemical catalysts. Abstract : Almighty : A powerful approach is introduced to prepare varied QDs/MC nanoplates by adopting corn straw piths as ideal biomass. A synthetic mechanism is proposed and investigated in depth. From this, Ni, Co, Cu, and MnO QDs/MC are successfully obtained. As a typical example, Ni QDs/MC nanoplates exhibit amazing capacitive performance.